Comparison of Personnel Reform of the United States and Australia - Shinta Maharani; Effy Zalfiana Rusfian (Journal of Social Research, 2023)
The role and function of the personnel system in the bureaucracy of a country is a critical, strategic, and decisive success factor. The size and quality of a country's bureaucracy determines whether it is superior or poor. For this reason, bureaucratic ability to change is needed in order to grow thoroughly and consistently, one of which is through research on best practices of personnel reform in other countries. This study aims to conduct benchmarking/comparative analysis of personnel system reform in the United States and Australia, which is based on the development of their respective staffing systems, using qualitative research methods and data collection techniques from literature studies. Position, job classification, and compensation, as well as training and development; to be used as comparison and assessment information. Based on the findings of this comparative study, each reform of the State Civil Apparatus has its own advantages and disadvantages.